Abortion Legislation and its Reform: A Cross Sectional Study on the Views of Obstetricians and Gynecologists in Nepal - Aryal, Shreyashi; Shrestha, Deepak (Nepal Journal of Obstetrics and Gynaecology, 2022)
Aims: To assess the knowledge of obstetrician and gynaecologists in Nepal about abortion legislation and to know their perception on its reform.Methods: A cross-sectional survey design was adopted. An online questionnaire was sent to all members of the Nepal Society of Obstetrician and Gynaecologists and response was collected. Profile of the respondents, their knowledge on the 2002 abortion legislation and their attitude on its reform were noted.Results: The response rate was 10.1%. There was a fair knowledge of previous abortion legislation amongst the 43 respondents. The mean score for the knowledge on previous abortion law and its reform was 3.85±0.35 and 3.0±1.14 respectively. Twenty-seven (62.8%) respondents felt the need for reform was necessary. In regards to the reform, 44.25% (19) stood for it and 46.5% (20) were against it. More (55%) obstetrician and gynaecologists practicing in the Bagmati province were against the reform.Conclusions: Obstetrician and gynaecologists practitioners in Nepal have a good knowledge of abortion legislation and are aware of its reform. The need for reform is also perceived well but there is a divided opinion amongst practitioners, with half of them positive about the reform and half standing against it.